Echocardiographic Evaluation of Left Ventricular Mass Among Adult Bangladeshi Population (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Left Ventricular Mass (LVM) refers to the weight of the left ventricle, which is determined using echocardiography. Various studies regarding LVM were conducted in different countries. There is a lack of data on LVM in our country. The current study aimed to provide baseline normative data on LVM among the adult Bangladeshi population.Materials and methods: This descriptive cross-sectional study included 100 adults who had normal echocardiography from the Outpatient Department of Cardiology and Medicine of Chittagong Medical College Hospital.   Results: Overall, LVM ranged from 63.90 gm to 186.58 gm with a mean ±SD of 123.55±24.38gm. The mean ± SD of LVM in males was significantly higher than female (136.30±20.65 vs. 110.80±21.03 gm, p